Pyroptosis and Intervertebral Disc Degeneration: Mechanistic Insights and Therapeutic Implications - Ge Y; Chen Y; Guo C; Luo H; Fu F; Ji W; Wu C; Ruan H (Dove Medical Press, 2022)
Yuying Ge,1,* Yuying Chen,2,* Chijiao Guo,1,* Huan Luo,3 Fangda Fu,1,4 Weifeng Ji,1,4 Chengliang Wu,1,4 Hongfeng Ruan1,4 1The First Clinical Medical College of Zhejiang Chinese Medical University, Hangzhou, 310053, People's Republic of China; 2The Fourth Clinical Medical College, Zhejiang Chinese Medical University, Hangzhou, People's Republic of China; 3Department of Pharmacy, The Second Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, People's Republic of China; 4Institute of Orthopaedics and Traumatology, The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Traditional Chinese Medicine), Hangzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Chengliang Wu, Institute of Orthopaedics and Traumatology, The First Affiliated Hospital of Zhejiang Chinese Medical University, 548 Binwen Road, Hangzhou, 310053, People's Republic of China, Email wcl@zcmu.edu.cn Hongfeng Ruan, Institute of Orthopaedics and Traumatology, The First Affiliated Hospital of Zhejiang Chinese Medical University, 548 Binwen Road, Hangzhou, 310053, People's Republic of China, Email rhf@zcmu.edu.cnAbstract: Low back pain (LBP) is a common problem worldwide, resulting in great patient suffering and great challenges for the social health system. Intervertebral disc (IVD) degeneration (IVDD) is widely acknowledged as one of the key causes of LBP. Accumulating evidence suggests that aberrant pyroptosis of IVD cells is involved in the pathogenesis of IVDD progression, however, the comprehensive roles of pyroptosis in IVDD have not been fully established, leaving attempts to treat IVDD with anti-pyroptosis approaches questionable. In this review, we summarize the characteristics of pyroptosis and emphasize the effects of IVD cell pyroptosis on the pathological progression of IVDD, including secretion of cytokines, nucleus pulposus cell apoptosis and autophagy, accelerated extracellular matrix degradation, annulus fibrosus rupture, cartilage endplate calcification, vascularization, sensory and sympathetic fiber neoinnervation, and infiltrating lymphatic vessels. Finally, we discuss several interventions used to treat IVDD by targeting pyroptosis. This review provides novel insights into the crucial role of IVD cell pyroptosis in IVDD pathogenesis, and could be informative for developing novel therapeutic approaches for IVDD and LBP.Keywords: low back pain, intervertebral disc degeneration, pyroptosis, inflammasome, anti-pyroptotic approach